The Influence of Organizational Citizenship Behavior (OCB) and Organizational Commitment on Employee Performance in the Representative Office of BKKBN of Bangka Belitung Islands Province - Triana, Mika; Hamsani, Hamsani; Widokarti, Joko Rizkie (Pusat P2M Politeknik Negeri Batam, 2024)
In the dynamic landscape of modern organizations, the endeavor to enhance employee performance continues to be a primary focus for managers and leaders, while is an increasing acknowledgment of the significance of intangible factors such as Organizational Citizenship Behavior (OCB) and Organizational Commitment in influencing employee performance. Therefore, this study aims to investigate and assess the impact of OCB and organizational commitment on employee performance within the Representative Office of BKKBN of Bangka Belitung Islands Province. Employing a quantitative methodology and utilizing questionnaires as data collection tools, the research utilized a saturated sampling method, encompassing all employees as the study's sample, comprising a total of 104 respondents. The investigation employed multiple linear regression analysis to examine the influence of OCB and organizational commitment on employee performance. The findings suggest that both OCB and organizational commitment exert a positive and statistically significant impact on employee performance, whether considered independently or concurrently. The findings of this study offer insights into factors influencing employee performance and offer practical recommendations for management to enhance OCB and organizational commitment, thereby improving overall employee performance.